Benefits of selective vitamin D receptor activators in kidney transplanted patients - Ferreira,Aníbal (2015)
Severe chronic kidney disease may lead to disturbances, such as hyperphosphatemia, increased secretion of fibroblast growth factor-23 (FGF-23) and vitamin D deficiency. These may increase plasmatic levels of parathyroid hormone, and decrease plasmatic levels of calcium. Altogether, these may contribute to the development of secondary hyperparathyroidism, and to abnormalities in mineral metabolism. Kidney transplantation is the best option to improve longevity and quality of life in end-stage chronic kidney disease patients. Vitamin D deficiency has been associated with cardiovascular disease, which is the leading cause of death in chronic kidney disease. Therefore, diagnosing this deficiency may be pivotal for minimizing mortality in chronic kidney disease, because pharmacological treatments for this deficiency may be prescribed. Calcitriol is indicated for the treatment of vitamin D deficiency, both in chronic kidney disease and in kidney transplanted patients. However, calcitriol may increase the plasmatic levels of calcium and phosphorous, which can lead to vascular calcifications, that have been associated with cardiovascular mortality. Selective vitamin D receptor activators are indicated for the treatment of vitamin D deficiency in chronic kidney disease. These have the advantage of being associated with lower increases of plasmatic levels of calcium and phosphorous. These drugs also seem to have additional effects that may minimise patient morbidity and mortality, especially due to potentially reducing cardiovascular events. Unfortunately, there are few studies about the use of these drugs in kidney transplanted patients. Here we present a review about the physiology of vitamin D, the consequences of its deficiency in chronic kidney disease and in kidney transplanted patients, and about the diagnosis and treatment of this deficiency. Finally, we discuss the new line of research about the efficacy and safety of selective vitamin D receptor activators in kidney transplanted patients